2023
DOI: 10.3390/nano13222941
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Cr-Nb-B Magnetic Particles and Adipose-Derived Mesenchymal Cells Trigger Cancer Cell Apoptosis by Magneto-Mechanical Actuation

Horia Chiriac,
Anca Emanuela Minuti,
Cristina Stavila
et al.

Abstract: Magnetic nanoparticles (MPs) are emerging as powerful and versatile tools for biotechnology, including cancer research and theranostic applications. Stem cell-mediated magnetic particle delivery has been previously recognized as a modality to target sites of malignancies. Here, we propose the use of adipose-derived mesenchymal cells (ADSC) for the targeted delivery of Fe-Cr-Nb-B magnetic particles to human osteosarcoma (HOS) cells and magneto-mechanical actuation (MMA) for targeting and destroying HOS cells. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Our recent studies 6 showed that a concentration of 1 mg/mL of magnetic nanoparticles provided to cells was the most effective for magnetomechanical actuation. Considering the high amount of drug for both MTX and DOX of 7% w/w adsorbed on MPs, it was decided to reduce the dose of chemotherapeutic compound to 1 and 10 μg for each milligram of MPs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our recent studies 6 showed that a concentration of 1 mg/mL of magnetic nanoparticles provided to cells was the most effective for magnetomechanical actuation. Considering the high amount of drug for both MTX and DOX of 7% w/w adsorbed on MPs, it was decided to reduce the dose of chemotherapeutic compound to 1 and 10 μg for each milligram of MPs.…”
Section: Resultsmentioning
confidence: 99%
“…The cellular uptake of nanomaterials is represented by several mechanisms such as endocytosis, phagocytosis, micropinocytosis, direct diffusion, and adhesive interactions. 26 Our recent studies 6 showed that a concentration of 1 mg/ mL of magnetic nanoparticles provided to cells was the most effective for magnetomechanical actuation. Considering the high amount of drug for both MTX and DOX of 7% w/w adsorbed on MPs, it was decided to reduce the dose of chemotherapeutic compound to 1 and 10 μg for each milligram of MPs.…”
Section: Internalization Of Drug-loaded Nanoparticlesmentioning
confidence: 99%
See 3 more Smart Citations